The Impact of Psychosocial Assistance Services on the Social Functioning of Children with Disabilities at the Indonesian Children's Cancer Foundation Jakarta - Saputro, Muhammad Andri; Rahman , Irhamni (Riviera Publishing, 2025)
Children with cancer not only face physical challenges due to long-term treatment, but also psychosocial pressures that affect their quality of life and growth and development process. For this reason, psychosocial assistance services are very important as a form of non-medical support that can help children adapt to disease conditions and maintain their social functioning. This study aims to analyze the impact of psychosocial assistance organized by the Indonesian Child Cancer Foundation (YKAI) Jakarta on the social functioning of children with cancer. The theoretical foundations used include psychosocial mentoring and guidance theory, social functioning theory, and intervention approaches such as bibliotherapy, play therapy, and art therapy. The research method uses a descriptive qualitative approach with in-depth interviews, observation, and documentation techniques. The research informants consisted of children with cancer, parents, and foundation social workers. The results of the study showed that mentoring services in the form of personal consultations, educational group activities, emotional monitoring, and family interventions had a positive impact on children. Children show increased self-confidence, communication skills, social skills, and optimism in the face of treatment, while families feel emotional support that strengthens their role in mentoring. This study concludes that psychosocial services contribute significantly to improving the social functioning of children with cancer, while emphasizing the importance of synergy between foundations, families, social workers, and the government in building a more comprehensive support system.